PENGARUH OLAHRAGA TERHADAP KESEHATAN MENTAL SISWA SEKOLAH MENENGAH DI SMKN 2 PANDEGLANG - M. Ghazwa Isha Firdaus; Ibnu Sina; Raden Akhmad Atqoo; Khofif Fauzi; Yogi Nurrohim; Galih Septiansyah Firdaus (CV. Denasya Smart Publisher, 2025)
This study aims to examine the influence of sports on the mental health of students at SMKN 2 Pandeglang. Mental health is an important aspect in supporting the learning process and the development of adolescents, while sports are believed to have a positive impact on students' psychological well-being. The study uses a qualitative approach with observation and in-depth interviews conducted with students and physical education teachers at the school. The data were analyzed descriptively to understand students’ perceptions and experiences regarding sports and their mental well-being. The results show that regular participation in sports activities contributes to reducing stress, improving mood, and enhancing students’ learning concentration. In addition, sports also strengthen social relationships among students, which further supports better mental health. This study concludes that sports play a significant role in improving the mental health of secondary school students, thus schools need to encourage and facilitate sports activities optimally.